Isolation and characterization of docosahexaenoic acid producing Thraustochytrids from mangrove ecosystem - Nurlaili Humaidah; Wirdhatul Muslichatin; Dyah Setyawati; Niniek Fajar Puspita; Satoshi Nakai; Sasanti Bhekti Purwasih; Nurhalida Listiani Putri (Konversi, 2025)
Polyunsaturated Fatty Acids (PUFAs) are unsaturated fatty acids that include DHA fatty acids. The conventional source of DHA is derived from various species of fish in the form of fish oil. DHA content in fish oil is relatively low, ranging from 7-14%, which necessitates the use of large quantities of fish, potentially leading to overfishing. Alternative source of DHA can be obtained through the isolation of thraustochytrids. Thraustochytrids can produce relatively higher levels of DHA and does not require extensive land areas for cultivation. This study aims to identify applicable techniques for isolating and identifying Thraustochytrid strains local to mangrove areas in East Java, `to examine the growth and general fatty acid profile, and to identify the most effective methods for controlling contamination during Thraustochytrid growth. The isolation involved several steps, including sample preparation, isolation, pure culture development, and media control by adjusting pH and temperature. Visual observations were made using an inverted microscope to confirm the presence of Thraustochytrids followed by genetic analysis to identify the strain. The optimal growth was observed in L3P sample collected from brown mangrove leaves. The highest specific growth rate was 0.146 h-1 (L3P). DHA content was 172 mg/g from the dried cell weight biomass. The most effective method for isolation involved a pre-treatment step consisting of soaking the samples in pine pollen for 8-10 days. Thraustochytrid isolates were able to grow in media with a pH of 7 and at a temperature of 25°C.